KETERSEDIAAN DAN PEMBENAHAN INFRASTRUKTUR DALAM MENCIPTAKAN IKLIM INVESTASI YANG KONDUSIF DI INDONESIA - T Ade Surya; Achmad Wirabrata (Jurnal Ekonomi & Kebijakan Publik, 2010)
Infrastructure is one of the important factors necessary to promote the economic development of a State. The progress of a country synonymous with the availability of adequate infrastructure development across the region so that socio‐economic progress can be felt fully by all levels of society. Indonesia's infrastructure impropriety caused by the relatively low investment in infrastructure sector. In addition, the persistence of the gap magnitude and quality of infrastructure investment flows are very prominent among the areas in Indonesia is another problem faced. Inhibition of development of infrastructure sector so far due to limitations on the government. Funds needed to build this sector is quite large, while the government should also allocate funds for development purposes in the areas other. To overcome this, the government should embrace other parties who have interests in infrastructure development. Public‐private partnership scheme which has been developed by the government during these should be implemented more seriously, considering that this scheme is one way out for the government to overcome budget limitations.